Temporal‐Scale Analysis of Environmental Controls on Sea Spray Aerosol Production Over the South Pacific Gyre. Issue 16 (24th August 2018) - Dror, Tom; Lehahn, Yoav; Altaratz, Orit; Koren, Ilan
Abstract: An understanding of sea spray aerosol (SSA) production is needed to better assess its influence on climate. Using satellite data, we investigated the production of the coarse mode of aerosol optical depth (AODc ), a proxy for SSA, over the pristine South Pacific Gyre. The analysis was done on three time scales: daily, seasonal, and interannual. Scale‐dependent links were shown between the AODc and wind speed (W). AODc and W were positively correlated on both daily and interannual time scales but were significantly anticorrelated on the seasonal time scale. Seasonality of the AODc − W link suggests contribution of other environmental factors. The main variable that could statistically explain trends in AODc on the seasonal time scale was chlorophyll a concentration, which showed a clear negative correlation with AODc . The AODc yield per W unit was clearly reduced when chlorophyll a concentration was high, suggesting a secondary, but important influence of marine biological activity on SSA production. Plain Language Summary: In this study we conduct temporal‐scale analysis on satellite data to explore the environmental factors that impact sea spray particles production. We focus on the South Pacific Ocean, which is a pristine marine environment and is characterized by low biological activity. The production of sea spray particles, that is wind‐driven process, is shown to be affected by the state of the marine biological activity (detected best on a seasonal time scale). High biological activity is suggested as a secondary influence that suppresses particles' production. This discovery is important for estimates of marine particles' budgets and effects and will enable better representation of marine aerosols in climate models. Key Points: Time scale‐dependent links are shown between sea spray aerosol amount and surface wind speed, with an anticorrelation on a seasonal scale Seasonality in the link between sea spray amount and surface wind speed indicates of additional factors that impact sea spray aerosol production Marine biological activity is suggested to be a secondary influence that suppresses sea spray aerosol production